2021
DOI: 10.1093/ehjqcco/qcab086
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation for patients with heart failure: association with readmission and mortality risk

Abstract: Aims To examine the temporal trends and factors associated with national CR referral and compare the risk of hospital readmission and mortality in those referred for CR versus no referral. Methods and Results This cohort study includes all adult patients alive 120 days from incident HF identified by the Danish Heart Failure Register (n = 33,257) between 2010 and 2018. Multivariable logistic regression models were used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 43 publications
1
25
0
3
Order By: Relevance
“…issues with transport, convenience, conflicts with return to work). [3][4][5] Furthermore, some patient groups are at lower likelihood of participating in CR, including older people, those living in greater social deprivation, and people from minority ethnic groups. 5 A key potential solution to improving CR access is more innovative, diverse models of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…issues with transport, convenience, conflicts with return to work). [3][4][5] Furthermore, some patient groups are at lower likelihood of participating in CR, including older people, those living in greater social deprivation, and people from minority ethnic groups. 5 A key potential solution to improving CR access is more innovative, diverse models of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Хронічна серцева недостатність (ХСН) залишається однією з головних причин смерті та непрацездатності населення, є кінцевою стадією серцево-судинного континуума [1]. Так, 5-10 % хворих вмирають протягом госпіталізації, ще 15 % -впродовж наступних 3 місяців, а більша частина пацієнтів -упродовж 5 років від часу маніфестації захворювання [2].…”
Section: Discussionunclassified
“…У нашому дослідженні ХСН збФВЛШ на тлі НМТ та ожиріння при супутній ФП встановили схильність хворих до анемізації, яку виявляли за вірогідно нижчими показниками гемоглобіну (на 4,3 %) та еритроцитів (на 7,9 %) паралельно з меншими значеннями лімфоцитів (на 18,1 %). Ці дані збігаються з висновками інших авторів, які виявили подібні зміни в таких пацієнтів, а зниження гемоглобіну, кількості еритроцитів і лімфоцитів вважали предикторами тяжчого перебігу та наслідків ХСН [1,3,4]. Супутня ФП у хворих на ХСН збФВЛШ із НМТ та ожирінням асоціювалась із достовірним переважанням вмісту сегментоядерних нейтрофілів (на 8,5 %), що, на думку дослідників, може відбивати виразність хронічного запального процесу [6].…”
Section: обговоренняunclassified
See 1 more Smart Citation
“…A large European study demonstrated that a referral to cardiac rehabilitation after a diagnosis of heart failure was associated with decreased hospital readmission and mortality. 114 In contrast, 1 of the most important recent randomized controlled trials, REHAB-HF, demonstrated that a tailored cardiac rehabilitation intervention can have a significant impact on physical outcome measures but not on overall outcomes including rehospitalization or death. 115 Even telehealth rehabilitation programs have shown that, while short-term positive gains are made, there was no lasting effect on preventing admission or mortality.…”
Section: Preoperative Anemiamentioning
confidence: 99%